One-pot synthesis of 2-azolylimidazole derivatives through a domino addition/A3 coupling/cyclization process under copper catalysis. Issue 7 (6th February 2020) - Lin, Yifan; Li, Erfei; Wu, Xin; Wang, Luyu; Wang, Haofeng; Li, Xiaoyu; Kang, Honglan; Zhou, Liejin; Shen, Guodong; Lv, Xin
Abstract : A novel one-pot approach for the synthesis of multi-substituted 2-imidazolylimidazoles, 2-pyrazolylimidazoles and 2-indazolylimidazoles was developed through a domino addition/A 3 coupling/cyclization process under copper catalysis. Abstract : A novel one-pot approach for the synthesis of multi-substituted 2-imidazolylimidazoles, 2-pyrazolylimidazoles and 2-indazolylimidazoles was developed through a domino addition/A 3 coupling/cyclization process under copper catalysis. A variety of aminoethyl- or hydroxylethyl-tethered 2-azolylimidazole derivatives were conveniently and efficiently assembled in one pot using N -propargylcarbodiimides, azoles, paraformaldehyde and secondary amines as starting materials. The products containing an o -iodoaryl group could be further converted to imidazo[1, 2- c ]imidazo[1, 2- a ]quinazoline derivatives through a copper-catalyzed intramolecular C–H arylation.